2023
DOI: 10.3390/nano13050827
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fabrication of Mn-Doped NiMoO4 Rod-like Arrays as High Performance OER Electrocatalyst

Abstract: The slow kinetics of the oxygen evolution reaction (OER) is one of the significant reasons limiting the development of electrochemical hydrolysis. Doping metallic elements and building layered structures have been considered effective strategies for improving the electrocatalytic performance of the materials. Herein, we report flower-like nanosheet arrays of Mn-doped-NiMoO4/NF (where NF is nickel foam) on nickel foam by a two-step hydrothermal method and a one-step calcination method. The doping manganese meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In the chemical industry, many reaction processes are required to be conducted under high-temperature, high-pressure, or strongly corrosive conditions. Silicon carbide, because of its exceptional chemical stability, high-temperature resilience, and excellent thermal conductivity, emerges as an ideal material for manufacturing chemical reactors. SiC reactors are capable of handling highly corrosive chemicals such as strong acids and bases, as widely applied in the production of silicates, fertilizers, and dyes and in the refining and petrochemical industries. Compared to traditional materials, SiC reactors provide higher thermal efficiency, reduce energy consumption, and, due to their outstanding corrosion resistance, significantly lower maintenance costs and downtime.…”
Section: Application Of Sic In Acidic and Alkaline Environmentsmentioning
confidence: 99%
“…In the chemical industry, many reaction processes are required to be conducted under high-temperature, high-pressure, or strongly corrosive conditions. Silicon carbide, because of its exceptional chemical stability, high-temperature resilience, and excellent thermal conductivity, emerges as an ideal material for manufacturing chemical reactors. SiC reactors are capable of handling highly corrosive chemicals such as strong acids and bases, as widely applied in the production of silicates, fertilizers, and dyes and in the refining and petrochemical industries. Compared to traditional materials, SiC reactors provide higher thermal efficiency, reduce energy consumption, and, due to their outstanding corrosion resistance, significantly lower maintenance costs and downtime.…”
Section: Application Of Sic In Acidic and Alkaline Environmentsmentioning
confidence: 99%
“…[4][5][6] Different from the HER, it is known that the OER process encounters significant kinetic hindrance as it involves a four-electron process. 7 Numerous studies have demonstrated that Ir-based and Rubased catalysts are excellent OER catalysts and can effectively enhance the catalytic activity in the OER. 8 However, as noble metals, the scarcity and high price of Ir and Ru seriously restrict their widespread use.…”
Section: Introductionmentioning
confidence: 99%